Análisis de caso en un paciente que padece síndrome de kwashiorkor - Bohórquez Suarez, Gina Lissette; Cuenca Tinoco, Jessica Carla (Machala : Universidad Técnica de Machala, 2019)
Acute malnutrition affects children under 5 years of age around the world, approximately 9 million children under 5 die and a third of these deaths were due to malnutrition. This type of Kwashiorkor malnutrition or Kwashiorkor Syndrome is a systemic disease. It occurs for several reasons: by a low availability of proteins, the poor intake of these, due to inadequate absorption, also develop by early weaning of the maternal breast, by not compensating the adequate amounts of proteins and in some people suffering from a chronic and / or severe disease. In this syndrome, the most vulnerable groups are children under 2 years. It is manifests apathy, slowing growth, loss of body mass , and the characteristic sign is edema and frequent infections of the respiratory and digestive tracts, for our titration work we have set ourselves the objective of analyzing the clinical case of the patient suffering from Kwashiorkor syndrome, using the Virginia Henderson model to improve its quality of life. To develop our case analysis we implemented a qualitative methodology. It was carry out by, the observation of clinical manifestations while hospitalized, and in addition to the collection of information from the clinical history of the study object, from the literature review, of updated national and international scientific studies and articles. The results of the study are of a 1-year-old 2-month-old girl from the Barbones parish in the canton of El Guabo, who enters the Pediatric Emergency Unit of the Machala General Hospital, in the company of the maternal grandmother. She said that the girl presents cough of moderate intensity, in addition epistaxis and streaks of blood on deposition, with 12 hours of evolution. When investigating the clinical history, the girl had a personal pathological history: Infantile Cerebral Palsy, Moebius Syndrome, had a colostomy, more presence of functional gastrostomy and in her family pathological antecedents: Maternal grandmother suffers from diabetes and her maternal uncle lupus erythematosus. In the time of the interview, the maternal grandmother states that the girl did not receive exclusive breastfeeding. In addition, the girl have recurrent respiratory tract infections. In the physical examination she was rated restless patient, with apathy, a persistent moan, irritable wet cough, secretions abundant, rhinorrhea, intercostal circulation, globular abdomen, depressible not painful to palpation with the presence of functional gastrostomy, decreased muscle mass, edema of lower limbs. Based on the research conducted for this study. We can conclude that Kwashiorkor Syndrome is a type of severe malnutrition that affects children under 2 years of age and especially premature children and have not received the necessary nutrients to its effective development. The multidisciplinary health team recommends the prevention of Kwashiorkor Syndrome as it can cause irreparable consequences in the infant and in extreme cases leads to the death of the child.
La desnutrición infantil aguda afecta a los menores de 5 años alrededor del mundo, aproximadamente 9 millones de niños menores de 5 años mueren y una tercera parte de estas muertes fueron a causa de la desnutrición. La desnutrición tipo Kwashiorkor o Síndrome de Kwashiorkor es una enfermedad sistémica, producida por una baja disponibilidad de proteínas, la ingesta escasa de estas, por una inadecuada absorción, también se desarrollan por el destete temprano del seno materno, por no compensar las cantidades adecuadas de proteínas y en ciertos casos se presenta en las personas que padecen alguna enfermedad crónica y/o grave, en este síndrome los grupos más vulnerables son los niños menores a los 2 años y se manifiesta con apatía, desaceleración del crecimiento, pérdida de la masa corporal, y el signo característico es el edema e infecciones frecuentes del tracto respiratorio y digestivo, para nuestro trabajo de titulación nos hemos planteado como objetivo analizar el caso clínico de la paciente que padece síndrome de Kwashiorkor, mediante el modelo de Virginia Henderson para mejorar su calidad de vida. Para desarrollar nuestro análisis de caso se implementó una metodología cualitativa, la misma que se realizó mediante: la observación de las manifestaciones clínicas mientras permaneció hospitalizada, y además de la recopilación de información de la historia clínica del objeto de estudio, de la revisión bibliográfica, de estudios y artículos científicos nacionales e internacionales actualizados. En los resultados del estudio se trata de una niña de 1 año 2 meses de edad, oriunda de la parroquia Barbones del cantón El Guabo, la misma que ingresa a la unidad de Emergencia Pediátrica del Hospital General Machala, en compañía de la abuela materna la misma que refiere que la niña presenta tos de moderada intensidad, además epistaxis y deposiciones con estrías de sangre, con 12 horas de evolución. Al indagar en la historia clínica la niña presenta antecedentes patológicos personales: Parálisis Cerebral Infantil, Síndrome de Moebius, tenía una colostomía, más presencia de gastrostomía funcional y en sus antecedentes patológicos familiares: Abuela materna padece de diabetes y su tío materno lupus eritematoso. Al momento de la entrevista abuela materna manifiesta que la niña no recibió lactancia materna exclusiva y que la niña presenta infecciones de tracto respiratorio recurrentes, mientras que en el examen físico se valoró paciente intranquila, con apatía, un quejido persistente, tos húmeda irritativa, secreciones abundantes, rinorrea, tiraje intercostal, abdomen globuloso, depresible no doloroso a la palpación con presencia de gastrostomía funcional, disminución de la masa muscular, edema de miembros inferiores. Basándonos en la investigación realizada para este estudio, podemos concluir que el Síndrome de Kwashiorkor es un tipo de desnutrición severa que afecta a los menores de 2 años y especialmente a los niños que han sido destetados antes de tiempo y no han recibido los nutrientes necesarios para su desarrollo eficaz, es por ello que el equipo multidisciplinario de salud recomienda la prevención del Síndrome de Kwashiorkor ya que puede provocar secuelas irremediables en el infante y en caso extremos conlleva a la muerte del menor.
Keywords: SINDROME DE KWASHIORKOR; SINDROME DE MOEBIUS; LUPUS; COLOSTOMIA